2019
DOI: 10.3390/rs11182158
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Pointing Angle Calibration Method for the Spaceborne Photon-Counting Laser Altimeter Based on Small-Range Terrain Matching

Abstract: The satellite, Ice, Cloud and Land Elevation Satellite-2 (ICESat-2) has been equipped with a new type of spaceborne laser altimeter, which has the benefits of having small footprints and a high repetition rate, and it can produce dense footprints on the ground. Focusing on the pointing angle calibration of this new spaceborne laser altimeter, this paper proposes a fast pointing angle calibration method using only a small range of terrain surveyed by airborne lidar. Based on the matching criterion of least elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The main steps include two steps: firstly, terrain matching is used to obtain the common terrain feature points whose coordinate deviations are used as input observations, and the second step is to calculate the system calibration parameters by laser beam adjustment. As shown in Figure 10, the specific solution can be simplified to calibrate two pointing angular parameters (θ 0 , β 0 ) and 1 range parameter r. It has been shown that the angular calibration accuracy is better than 0.3 arc second using 1 km length laser line matched with high-precision terrain, and the angular calibration accuracy is better than 0.1 arc second when the line length is increased to 2.5 km [52]. In addition, ICESat-2 adopts a similar strategy to ICESat for attitude maneuvering in the oceanic region, and the attitude and distance are calibrated separately by conical scanning, and the long-term drift of the calibrated range values is less than 1 mm/year [53].…”
Section: Lidar Parameters Calibrationmentioning
confidence: 99%
“…The main steps include two steps: firstly, terrain matching is used to obtain the common terrain feature points whose coordinate deviations are used as input observations, and the second step is to calculate the system calibration parameters by laser beam adjustment. As shown in Figure 10, the specific solution can be simplified to calibrate two pointing angular parameters (θ 0 , β 0 ) and 1 range parameter r. It has been shown that the angular calibration accuracy is better than 0.3 arc second using 1 km length laser line matched with high-precision terrain, and the angular calibration accuracy is better than 0.1 arc second when the line length is increased to 2.5 km [52]. In addition, ICESat-2 adopts a similar strategy to ICESat for attitude maneuvering in the oceanic region, and the attitude and distance are calibrated separately by conical scanning, and the long-term drift of the calibrated range values is less than 1 mm/year [53].…”
Section: Lidar Parameters Calibrationmentioning
confidence: 99%
“…It is easy for later calibration processing. [4] Select the rotation speed and rotation direction, control the lower test bench motor to rotate continuously at the selected speed. After a week of rotation, end the experiment.…”
Section: Angle Measurement Experimentsmentioning
confidence: 99%
“…To evaluate the relationship between the inverse forest floor and airborne G-LiHT data at different laser intensities in the ATLAS data, the coefficient of determination (R 2 ), root mean square error (RMSE), and absolute mean error (MAE) at two laser intensities were separately statistically evaluated [11,[27][28][29]. To investigate the extent to which the vegetation canopy height and vegetation cover at different ATLAS laser intensities affected the accuracy of DTM inversions in the forest understory, we separately conducted inversions for different laser types within different canopy scales (zone groups), using the ATLAS ground photon elevations minus the corresponding elevations of airborne G-LiHT, and statistical indicators of errors by laser type (RMSE, R 2 , MAE number, and weight of different canopy heights (N)) [30,31].…”
Section: Accuracy Assessment Criteriamentioning
confidence: 99%